TAMAN BUDAYA KALIMANTAN BARAT DENGAN PENERAPAN KONSEP SUSTAINABLE DESIGN - Liuanda, Vilia Dharani; Khaliesh, Hamdil; Nurhamysah, Muhammad (JMARS: Jurnal Mosaik Arsitektur, 2025)
In West Kalimantan itself, there is a Taman Budaya Kalimantan Barat located in Pontianak City. In its development, this Cultural Park is less developed and no longer functions properly. In addition, another problem is the location of the Cultural Park, namely there is a flood problem. This problem is one of the big problems. Therefore, the Taman Budaya Kalimantan Barat was designed with a sustainable design concept approach. This design is expected to produce a Taman Budaya Kalimantan Barat design that has a new face to present culture and art in West Kalimantan. This design uses the method of J. C. Jones (1972). The method includes five stages, namely ideas, information, analysis, synthesis, evaluation and finally, optimization. This design produces a Cultural Park design that has 4 building masses. The arrangement of the Taman Budaya area uses the concept of Water Sensitive Urban Design (WSUD) which focuses on the management of the water cycle in the area which serves to overcome the problem of flooding in the area. The shape of the building mass of the Taman Budaya building takes the form of a circle which is taken to present a more flexible and open form, as well as a form that can connect other masses in the area. In the Taman Budaya building, not too many ornaments are used to keep the impression simple and blend in with other buildings.